Uji Perbandingan Penetapan Kadar Sediaan Tablet Allopurinol 300 mg Generik dengan Nama Dagang Beredar di Distrik Sentani, Jayapura - Rusnaeni Rusnaeni; Eva S. Simaremare (Jurnal Biologi Papua, 2019)
Allupurinol is a medicine to treat gout especially to minimize the quantity of uric acid inside human blood. This study aims to understand the quality of gout drugs particularly the standard of Allupurinol between generic 300 mg and others Allupurinol tablet in retails at Jayapura Regency. Survey method has been used and samples were collected from Sentani district, Jayapura Regency. Spectrophotometer was used to determine the rate of Allupurinol. The results proved that in Allupurinol generic (A) the rate was 100.28% and generic (B) was 99.044%. For others tablet non generic with naming (a) the rate of Allupurinol as 99.46% while (b) was 100.77%. It means the averages of Allupurinol contain in generic was 99.6% and non-generic was 100.12%. According to Indonesian Farmakope Manual 4th Edition, the rate of Allupurinol contains in a drug must be 93.0% for minimum and can’t be more than 107.0%. Our study shown that Allupurinol generic with (A) label and non-generic with (b) label are based on the Indonesian Farmakope Standard 4th Edition.  Key words: Tablet Allopurinol, Penetapan generik, Jayapura.